Avaliação do potencial inseticida de produtos naturais e sintéticos no controle das brocas da graviola. - Melo, Brisa do Svadeshi Cabral de (2006)
Sour sop, Annona muricata, is an Annonaceae specie crop that is growing gradually in the Northeast region of Brazil. Although it is difficult to handle, considering the control of its diseases and pests that occur to it is one in such a way how much complicated, this fact does not intimidate the producers of pulps, ices cream, juices, therefore the promising consuming market causes profit. The fruit borer, Cerconota anonella, and the seed borer, Bephratelloides spp are the most important pests that attack sour sop orchard. The seed borer is a very complex group which is found all growing areas around the world. Both represent the most important pests for their damage to the fruit and loss to growers. In spite of the economic importance played by sour sop, scientific studies to improve its growing methods are scarce. Considering these introduction, with the objective to evaluate the potential of natural and synthetic products in the control of the fruit and seed borers, an experiment was conducted in the Experimental Station of the Embrapa in Pacajus - Ce, from March to September of 2005. A completely randomized design was used in a 4x2x2 factorial, where four products had been used: natuneem, watery extract of Licania rigida, endosulfan (Thiodan CER Bayer CropScience) and Deltamethrin (Decis 25 CER, Bayer CropScience); two intervals of application; and fruit uncovered and covered with tissue-not-tissue (TNT) G-16, adding up to 18 treatments, each one with 9 replications. The Tukey test was used to compare the averages gotten for both insects, but it was necessary to use the Dunnet test in the results of fruit borer. For both pests the Abbbott test of efficiency was used. For the fruit borer, the covering fruit and application intervals did not affect the outcome of results. Deltamethrin and Endosulfan attained the highest efficiency for controlling the fruit borer (%E = 50,60). There were no differences on intervals of application and covering the fruit. The Treatments don’t showed satisfactory efficiency. On the order hand for the seed borer, covering the fruit was also significant. The Test of efficiency of Abbott pointed those treatments Licania extract applied every 28 days and uncovered fruit; endosulfan applied every 14 days + covered fruit; endosulfan applied every 28 days + covered fruit; deltamethrin applied every 14 days + covered fruit; deltamethrin applied every 14 days + uncovered fruit; deltamethrin applied every 28 days + covered fruit and deltamethrin applied every 28 days + uncovered fruit as higher percentages (%E = 39,51). The performance of the treatments against Bephratelloides spp. did not reached satisfactory percentage of efficiency.